The effect of combined non-pharmacological interventions on venous blood sampling pain in preterm infants: a clinical trial study - Fatemeh Yadollahzadeh; Zahra Akbarianrad; Seyedeh Roghayeh Jafarian-Amiri; Ali Zabihi; Parvin Aziznejadroshan; Hossein-Ali Nikbakht (BMC Pediatrics)
Abstract Background Using non-pharmacological methods to reduce the pain of hospitalized infants is one of the most important priorities in the health of newborns. Pain relief during painful procedures can help prevent unwanted physical and psychological effects. This study was conducted with the aim of investigating the effect of combined non-pharmacological interventions on venous blood sampling pain in preterm infants. Methods In this clinical trial study, 88 preterm infants admitted to the Neonatal Intensive Care Unit of Rouhani Hospital was randomly assigned to four groups of sucrose (S), the combined group of sucrose and non-nutritive sucking (NS), the combined group of swaddle and sucrose (SS) and the combined group of sucrose, non-nutritive sucking and swaddling (NSS). In order to collect information, were used the premature Infant Pain Profile Scale (PIPP) and demographic characteristics questionnaire. Results This study showed that during blood sampling, the difference in the mean pain score of two groups of S and NS was equal to 3.54 (95% CI = 1.85, 5.24) and in two groups S and NSS was equal to 4.68 (95% CI = 2.99, 6.38), and these differences were significant (P < 0.001). In addition, the mean pain difference in all study groups was significant in two time periods before-during and during-after blood sampling (P < 0.001). Also, the mean pain difference in the two time periods before-during and during-after in NS and NSS groups was significant compared to the control group (sucrose) (P < 0.001). Conclusions Based on the results of this study, the use of combined non-pharmacological interventions of NSS has been more effective in reducing the pain caused by venous blood sampling than other conditions where two or one non-pharmacological intervention were used.